Colonial Legacies: The American Museum of Natural History, the Theodore Roosevelt Equestrian Statue, and Public History - Nurse, Andrew (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2024)
In November 2021, the American Museum of Natural History (AMNH) announced that the Theodore Roosevelt equestrian statue would be moved from the museum’s entrance to the not yet completed Theodore Roosevelt Presidential Library in Medora, North Dakota. The statue depicts Roosevelt riding ahead of semi-clad walking figures of a Native American and an African man. Long the subject and site of protests, this relocation was not the museum’s first attempt to address public concerns. Activists suggested it be simply removed, but others argued that Roosevelt was a significant figure, he should not be judged by present standards, and the statue provides a chance for public education. In response to earlier protests, the AMNH created Addressing the Statue, an exhibition that explored the statue’s origins and meanings as well as alternatives to it. The exhibition was organized to create a self-contesting historical space in which the precise meaning of the past — and its commemoration — was debated and left open. This article explores the character and nature of this space. It argues that this approach failed and could not erase the politics of colonialism the statue embodied nor create a new conversation about history.